Sotah - Ragen, Naomi (Sifri Ltd, 1992)
Beautiful, fragile Dina Reich, a young woman in Jerusalem's ultra-Orthodox haredi enclave, stands accused of the community's most unforgivable sin: adultery. Raised with her sisters to be an obedient daughter and a dutiful wife, Dina secretly yearned for the knowledge, romance, and excitement that she knew her circumscribed life would never satisfy. When her first romance is tragically thwarted, she willingly enters into an arranged marriage with a loving but painfully quiet man. Dina's deeply repressed passions become impossible to ignore, finding a dangerous outlet in a sudden and intense obsession with a married man, with terrible consequences. Exiled to New York City, Dina meets Joan, a modern secular woman who challenges all she knows of the world and herself.
Keywords: Fiction; Women